EFFECTS OF POP CULTURE FOR IMPROVING STUDENT- TEACHERSâ WRITING SKILL (A CASE STUDY AT GALUH UNIVERSITY) - Ratnawati, Ratnawati (ELT Perspective Jurnal Pendidikan Bahasa Inggris, 2016)
Writing, one of the four skills which have to be taught by educators in language learning. Starting from classroom observation implied that students confronted the difficulties in writing involving generating ideas, organizing words, and making compositions. This study supposes to explore some effects of pop culture as authentic materials for English language teaching in improving studentsâ writing skill. Due to pop culture relates to studentsâ life and experience, it is considered to be a stimulus for gaining studentsâ ideas, information, motivation, and interest in teaching writing. The students of secondary school were involved in this study and descriptive case study was employed to observe the importance of pop culture in writing class. Also, questionnaires and studentsâ works are the instruments to measure its effects. Both studentsâ works and result of the questionnaires pointed out that significantly improvement obtained after applying pop culture. In line with findings, it can be said that pop cultures have significant effects toward studentsâ writing skill. So, educators need to apply pop culture as their choices in future planning lesson. Key words: Pop culture, Writing skill, Descriptive qualitative